Students' Anxiety In Speaking English At SMP Negeri 2 Tondano - Walalangi, Jovanka Syaloomitha; Liando, Nihta V. F; Rombepajung, Paula (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2025)
Students’ anxiety is a common challenge or concern faced by many students during the process of learning English as a foreign language. It is crucial to identify psychological factors early on before attempting to reduce and control them in order to address the potential mental block that may affect students' language learning process. The purpose of this research is to find out the factors which causes the students’ anxiety in speaking English at SMP Negeri 2 Tondano. This research used qualitive descriptive research method that will be done through interview and documentation. The subjects of this research consisted of 5 students of SMP Negeri 2 Tondano, and 1 triangulation. Based on the research findings and discussion, it can be concluded that three out of five students emphasized the factor Lack of Confidence as the predominant factor of anxiety in speaking English, meanwhile one student emphasized the factor Fear of Mistake as the predominant factor of anxiety in speaking English, and one student emphasized that Friends or Classmates as the predominant factor of anxiety in speaking English. In addition, a triangulation was interviewed regarding the five subjects, and all the subjects’ statement are proven to be valid.